THE MEASUREMENT OF OXYGEN FUGACITIES IN FLOWING GAS MIXTURES AT TEMPERATURES BELOW 1200°C - Beckett J.R.; Mendybaev R.A. (My University, 1997)
We measured oxygen fugacities in H2-CO2 and CO-CO2 gas mixtures in the temperature interval 700-1350°C using an yttria-stabilized zirconia (YSZ) oxygen sensor. At high temperatures in excess of 1200°C, measured emfs are consistent with expectations based on the gas composition. At lower temperatures in H2-CO2 gas mixtures, the oxygen fugacity (fO2) obtained assuming Nernstian behavior of the oxygen sensor is as much as two log units more reducing (#900°C) to one log unit more oxidizing (#700°C) than expected by assuming equilibrium speciation.The deviations in H2-CO2 gas mixtures arise from two sources: (1) poor contact between the electrode and the zirconia electrolyte, leading to apparent fO2 values that are higher than expected and (2) disequilibrium in the vapor, leading to lower than expected fO2 values in the temperature range #700-1200°C (for experiments near the iron-wustite (IW) buffer) and higher than expected fO2s at lower temperatures. The first problem can be alleviated by spring-loading and lightly sintering a Pt mesh internal electrode against the electrolyte and the second by forcing the entire gas stream to equilibrate by passing it through a Pt catalyst. With these measures, experiments employing H2-CO2 gas mixtures can be conducted routinely in the temperature range 700-1200°C and the fO2 determined with an accuracy comparable to that obtained at higher temperatures (2σ < +/-0.1 log units).Above #770°C, apparent oxygen fugacities measured using an oxygen sensor in CO-CO2 gas mixtures near IW are consistent with equilibration in the vapor regardless of whether or not a Pt catalyst is present. At lower temperatures, however, the measured values are more oxidizing than the expected equilibrium values. Under more reducing conditions, the deviations begin to occur at even higher temperatures, #930°C for IW-3. The anomalously high fO2 values are probably related to the condensation of graphite, which removes C from the gas and generates a lower temperature limit for practical gas mixing experiments using CO-CO2 gas mixtures.